Are statins 'IDEAL' for non-alcoholic fatty liver disease?. (February 2014) - Athyros, Vasilios G.; Katsiki, Niki; Karagiannis, Asterios; Mikhailidis, Dimitri P.
Abstract Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease and cause of elevated serum liver enzyme activities in the developed world1. Obesity, diabetes mellitus (DM), and dyslipidaemia, common components of the metabolic syndrome (MetS), are frequently associated with NAFLD; 75–100% of patients with MetS or DM have NAFLD2. NAFLD is characterized by hepatic triglyceride (TG) infiltration in the absence of alcohol abuse or chronic liver disease1. NAFLD includes a spectrum of conditions varying from steatosis to steatosis with inflammation [steatohepatitis (NASH)], necrosis, fibrosis or cirrhosis that rarely progresses to hepatocellular carcinoma3. NAFLD and NASH are the hepatic manifestations of MetS and are associated with increased cardiovascular disease (CVD) risk4. Most NAFLD/NASH patients die from CVD rather than from liver disease4, 5. There is no universally accepted treatment for NAFLD1-5.